Intercomparison of MAX-DOAS vertical profile retrieval algorithms: studies on field data from the CINDI-2 campaign - Tirpitz, Jan-Lukas; Frieß, Udo; Hendrick, François; Alberti, Carlos; Allaart, Marc; Apituley, Arnoud; Bais, Alkis; Beirle, Steffen; Berkhout, Stijn; Bognar, Kristof; Bösch, Tim; Bruchkouski, Ilya; et al. (Atmospheric measurement techniques, 2021)
The second Cabauw Intercomparison of Nitrogen Dioxide measuring Instruments (CINDI-2) took place in Cabauw (the Netherlands) in September 2016 with the aim of assessing the consistency of multi-axis differential optical absorption spectroscopy (MAX-DOAS) measurements of tropospheric species (NO2, HCHO, O3, HONO, CHOCHO and O4). This was achieved through the coordinated operation of 36 spectrometers operated by 24 groups from all over the world, together with a wide range of supporting reference observations (in situ analysers, balloon sondes, lidars, longpath DOAS, direct-sun DOAS, Sun photometer and meteorological instruments).